Lyme Disease - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
Revised! ENY-209, a 4-page illustrated fact sheet by P. E. Kaufman, P. G. Koehler, and J. F. Butler, describes this disease transmitted by the bite of a tick — symptoms, treatment, prevention, and control. Includes references. Published by the UF Department of Entomology and Nematology, August 2009.